A method for simultaneous gene overexpression and inactivation in the Corynebacterium glutamicum genome. (1st October 2016) - Xu, Jianzhong; Zhang, Junlan; Han, Mei; Zhang, Weiguo
Abstract: The gene integration method is an important tool to stably express desirable genes in bacteria. To avoid heavy workload and cost, we constructed a rapid and efficient method for genome modification. This method depended on a mobilizable plasmid, which contains a P tac promoter, an introduced multiple cloning site (iMCS), and rrnBT1T2 terminator. Briefly, the mobilizable plasmid pK18-MBPMT with the P tac -iMCS- rrnBT1T2 cartridge derived from pK18 mobsacB was prepared to directly integrate hetero-/homologous DNA into the Corynebacterium glutamicum genome. Like our previous method, this method was based on insertional inactivation and double-crossover homologous recombination, which simultaneously achieved gene overexpression and inactivation in the genome without the use of genetic markers. Compared to the previous method, this protocol omitted the construction of a recombinant expression plasmid and clone of the target gene(s) cassette, which significantly decreased the workload, cost, and operational time. Using this method, the heterologous gene amy and the homologous gene lysC T311I were successfully integrated into the C. glutamicum genome at alaT and avtA loci, respectively. Moreover, the operation time of this method was shorter than that of the previous method, especially for repeated integration. This method, which is based on the mobilizable plasmid pK18-MBPMT, thus represents a potentially attractive protocol for the integration of genes in the course of genetic modification of C. glutamicum .